1979
DOI: 10.1029/ja084ia12p07099
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetopause surface fluctuations observed by Voyager 1

Abstract: As Voyager 1 moved out of the dawnside of the earth's magnetosphere on September 5, 1977 (at position (−2.6, −16.5, 1.1) earth radii in GSE), it crossed the magnetopause apparently seven times, despite the high spacecraft speed of 11 km/s. Normals to the magnetopause and their associated error cones were well determined for each of the crossings through the use of a minimum variance analysis of the internal magnetic field. The oscillating nature of the ecliptic plane component of these normals indicates that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…Note also that when Geotail crosses the boundary layer during the time interval C, with relatively large clock angle, the position of Geotail near the equator and close to the stagnation region (Figure 1) is not the most favorable for meaningful comparison with the wave activity at Cluster . Moreover, to derive properties, including the phase speed, of wave activity at Geotail , would require a single spacecraft method as employed by Lepping and Burlaga [1979], which assumes a sinusoidal shape of the waves. For these reasons, we leave out the comparison between the two‐point observations at Cluster and Geotail during the time interval C.…”
Section: Resultsmentioning
confidence: 99%
“…Note also that when Geotail crosses the boundary layer during the time interval C, with relatively large clock angle, the position of Geotail near the equator and close to the stagnation region (Figure 1) is not the most favorable for meaningful comparison with the wave activity at Cluster . Moreover, to derive properties, including the phase speed, of wave activity at Geotail , would require a single spacecraft method as employed by Lepping and Burlaga [1979], which assumes a sinusoidal shape of the waves. For these reasons, we leave out the comparison between the two‐point observations at Cluster and Geotail during the time interval C.…”
Section: Resultsmentioning
confidence: 99%
“…Such waves may be common; for example, Lepping and Burlaga [1979] saw oscillations of the dawn magnetopause which they interpreted as surface waves of amplitude 1/3 Re, and wavelength 4 Re. These more regular pulsations, with a period of -4.5 min, die out at -7.2 Re at -1145 UT, as the average magnetic field strength climbs to near 100 nT.…”
Section: Interpretation Of the Event Seen On Iseementioning
confidence: 99%
“…Several studies have reported evidences of KH instability at the Earth's magnetopause since the early observation by Lepping and Burlaga (1979). These authors developed a method to infer the amplitude and the wavelength of the KH instability.…”
Section: Discussionmentioning
confidence: 99%